HUBUNGAN FAKTOR KESEHATAN LINGKUNGAN DENGAN KEJADIAN TUBERKULOSIS DI KOTA PADANG TAHUN 2023 - finy marsyah; Yuniar Lestari; Masrul Basyar (Jurnal Endurance, 2023)
Tuberculosis is still a public health problem both in Indonesia and internationally so that it is the goal of the SDGs. In 2021 the number of tuberculosis cases in Padang City was 1,656 cases, the cure rate decreased from 1009 to 457. The death toll increased from 75 to 93. This study aims to analyze environmental health factors associated with tuberculosis. The type of research is quantitative, comparative cross sectional study design. Respondents of the tuberculosis group were tuberculosis sufferers who had lived in the same house with the patient. The non-TB group is not a patient who has been at home with TB sufferers. Data was analyzed using chi square and logistic regression. This research was conducted at 5 Puskesmas in Padang City from June-July 2023. The study showed that 52.8% occupancy density, 45.8% ventilation, 37.5% lighting, 40.3% humidity respondents did not qualify, 98.6% of respondents' house floors were qualified. There are relationships between density (p = 0.034), ventilation (p = 0.005), lighting (p = 0.003), humidity (p = 0.04). The lighting variable is the most dominant variable related to the incidence of tuberculosis in Padang City in 2023. The variable most associated with tuberculosis incidence is lighting. This study found that ventilation is related to tuberculosis, so it needs to be considered in PBG (building approval) to establish rules on the minimum ventilation area requirements as one of the requirements in granting construction approval so that the house becomes healthy and protected from infectious diseases